1989
DOI: 10.1159/000138601
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro and in vivo Inhibition of Intestinal Heme Oxygenase by Tin-Protoporphyrin

Abstract: The effects of tin-protoporphyrin (SnPP) on the activity of heme oxygenase in the epithelium of the proximal region of the small intestine were examined in male Sprague-Dawley rats. A single dose of SnPP (25 µmol/kg body weight) administered either parenterally or by gavage-produced time-dependent decreases in the activity of microsomal heme oxygenase over 24–48 h. Although heme oxygenase activity reverted to normal levels within 24 h after oral dosing, parenteral treatment resulted in substantial (70%) inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Patients with increased iron due to hemochromatosis display increased serum ferritin levels [4,6,7], and it has been demonstrated recently that biliary secretion of iron and ferritin is increased during iron overload [8]. Also, administration of competitive inhibitors of heme oxygenase (HO), the rate-limiting en-zyme in the degradation of heme to bile pigments, such as Sn protoporphyrin (SnPP) and Sn mesoporphyrin (SnMP), leads to increased biliary secretion of undegraded endogenous and exogenous heme in animals and in man [8][9][10][11][12][13][14], inhibits intestinal HO activity, thus diminishing heme-iron uptake in the gut [15][16][17][18], and in prolonged use can produce a reversible iron deficiency state [18,19]. These effects of HO inhibitors are of interest in studies of the interrelationship of HO activity, heme degradation, iron metabolism and iron storage diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with increased iron due to hemochromatosis display increased serum ferritin levels [4,6,7], and it has been demonstrated recently that biliary secretion of iron and ferritin is increased during iron overload [8]. Also, administration of competitive inhibitors of heme oxygenase (HO), the rate-limiting en-zyme in the degradation of heme to bile pigments, such as Sn protoporphyrin (SnPP) and Sn mesoporphyrin (SnMP), leads to increased biliary secretion of undegraded endogenous and exogenous heme in animals and in man [8][9][10][11][12][13][14], inhibits intestinal HO activity, thus diminishing heme-iron uptake in the gut [15][16][17][18], and in prolonged use can produce a reversible iron deficiency state [18,19]. These effects of HO inhibitors are of interest in studies of the interrelationship of HO activity, heme degradation, iron metabolism and iron storage diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Under these assumptions, the levels of ZnBG found in the liver, intestine, kidney, and spleen, are within the concentration range expected to inhibit HO. This enzyme has been well characterized in rat and hu man tissues, with some of its highest activity in spleen, liver, and intestine [14,17,18]. Furthermore, hepatic and splenic HO activ ity peak shortly after birth in neonatal rats and humans [19,20], Thus, the tissue distri bution of ZnBG we report here after enteral administration seems appropriate to inhibit HO in neonatal tissues.…”
Section: Discussionmentioning
confidence: 71%
“…A very low degree of absorp tion of SnPP from the gastrointestinal tract after oral treatment of adult rats at 25 pmol/kg has been reported [14], It was also concluded that SnPP was not absorbed in human subjects who received oral doses of 0.25-5.0 pmol/kg, as SnPP was not present in their plasma or urine [11], In neonatal or adult rats neither SnPP nor ZnPP was able to inhibit hepatic or splenic HO after gastric gavage at 40 pmol/kg [15]. Furthermore, ZnPP was not significantly absorbed by the small intestine in preliminary studies under the experimental conditions described here [data not reported].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of heme degradation by agents such as SnMP leads to the prompt excretion into bile of unmetabolized heme [6,7], Since SnMP, administered parenterally or orally, can also potently inhibit intestinal heme oxy genase activity [8], the possibility is raised that the mechanism of development of iron deficiency anemia after prolonged SnMP ad ministration reflects, at least in part, dimin ished absorption of heme and thus of heme iron from the intestinal lumen.…”
Section: Introductionmentioning
confidence: 99%